Impacts of Palm Oil Mill Effluent (POME) on Water Quality in Nigeria: Challenges for Sustainable Development and Public Health - Edet, Eyo Orok; Effiong, Mfonobong; Udie , Elizabeth Akwenaboye; Odok, Gabriel Nku (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: To assess the environmental impact of Palm Oil Mill Effluent (POME) on water quality in Nigeria’s major palm oil processing hubs, and also evaluate how traditional palm oil processing practices hinder progress toward the United Nations' 17 Sustainable Development Goals (SDGs), particularly those related to clean water and health. Methodology/Approach: Field-based water quality assessment conducted at five major palm oil processing hubs: Edo, Akwa-Ibom, Cross River, Anambra, and Imo states. Physicochemical parameters measured included pH, conductivity, water hardness, nitrite, magnesium, BOD, TDS, TS, and WQI. Statistical analysis was performed using Pearson’s correlation coefficient to determine relationships between variables (e.g., conductivity and TDS, pH and hardness). Originality/Relevance: The study highlights a critical but under-researched environmental issue in Nigeria’s agro-industrial sector. Connects local environmental degradation to global sustainability goals, emphasizing the broader implications of untreated POME discharge. Offers region-specific insights that are essential for targeted policy and technological interventions Key Findings: pH values were within acceptable limits (6.5–8.5), but other parameters exceeded safe thresholds: High conductivity (800–1150 µS/cm) and water hardness (200–300 mg/L); Nitrite levels (10–45 mg/L) and magnesium content exceeded safe limits; BOD levels (75–290 mg/L) indicated significant organic pollution; TDS and TS levels were elevated, especially outside Edo State; WQI scores classified water quality as "poor" to "very poor." Borehole water contamination by sulfate, sodium, magnesium, and chloride discouraged its use for drinking. In addition, the study revealed strong positive correlation between conductivity and TDS (r = 0.85), and moderate correlation between pH and hardness (r = 0.65). Theoretical/Methodological Contributions: This demonstrates the utility of Water Quality Index (WQI) and Pearson’s correlation in environmental impact assessments. Provides a replicable framework for evaluating agro-industrial pollution in developing economies. The study contributes to environmental economics and public health literature by linking industrial waste management to SDG progress.